2012
DOI: 10.2967/jnumed.111.095398
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Tools for Measurements of Regional Stress and Rest Myocardial Blood Flow Assessed with 13N-Ammonia PET/CT

Abstract: Several models for the quantitative analysis of myocardial blood flow (MBF) at stress and rest and myocardial flow reserve (MFR) with 13 N-ammonia myocardial perfusion PET have been implemented for clinical use. We aimed to compare quantitative results obtained from 3 software tools (QPET, syngo MBF, and PMOD), which perform PET MBF quantification with either a 2-compartment model (QPET and syngo MBF) or a 1-compartment model (PMOD). Methods: We considered 33 adenosine stress and rest 13 N-ammonia studies (22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 17 publications
3
78
1
Order By: Relevance
“…for 13 N-ammonia 27 and 82 Rb, 28-30 but significant variation remains among some vendor programs. Further standardization of image acquisition and analysis methods will have the benefit of allowing reliable pooling of MBF data as part of large, multicenter clinical trials.…”
Section: Image Acquisition and Analysismentioning
confidence: 99%
“…for 13 N-ammonia 27 and 82 Rb, 28-30 but significant variation remains among some vendor programs. Further standardization of image acquisition and analysis methods will have the benefit of allowing reliable pooling of MBF data as part of large, multicenter clinical trials.…”
Section: Image Acquisition and Analysismentioning
confidence: 99%
“…Clinical protocols have been suggested for new promising compounds such as 18 F-flurpiridaz [7]. This fluorine-18-based tracer extends the possibilities of perfusion imaging implementation through a regional rather than on-site cyclotron due to its longer half-life (110 min).…”
Section: Pet Imaging Protocolsmentioning
confidence: 99%
“…Recently it was reported that even shorter acquisition time did not hamper the reproducibility of MBF measurement using 15 O water PET (28). However, MBF values can vary according to which tracers or methods are used (29,30). So, it is recommended that the same tracer, analytical method and software be used Cp (t), arterial input function; C1 (t), 13 N ammonia activity in the freely diffusible compartment; C2 (t), metabolically trapped 13 On the other hand, MBF is affected by many extrinsic factors including age, sex, heart rate, blood pressure and myocardial oxygen consumption (40).…”
Section: Ffr Vs Mbfmentioning
confidence: 99%